Opportunities And Challenges: Digital Transformation In Voluntourism - Khairune Nisa, An Nuur (Jurnal Toursci, 2024)
In the era of digital development, the voluntourism phenomenon has undergone significant changes along with technological transformation. Voluntourism has become a rapidly growing global phenomenon, combining travel with participation in volunteer activities to impact local communities positively. This study uses a qualitative method with a literature review approach to gain a deeper understanding of a phenomenon that has not been well-researched before. The data collection method used in this study is literature. Literature studies will be carried out by tracking documents, such as scientific journals, articles, and documents related to voluntourism and social media related to Voluntrip. The results of the literature review show that with the development of digital, Generation Z currently prefers tourism oriented towards the local environment and authentic tourism. This is because, in addition to having high social and environmental awareness, today's generation of young people wants a memorable experience. While digital technology provides opportunities for broader collaboration and participation, its massive use also brings challenges, primarily related to the risk of commodification. Commodification practices in voluntourism can result in the objectification of local communities, negatively impacting their psychological and economic well-being.